2018
DOI: 10.1007/s00248-018-1244-7
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Bacterial Maintenance Respiration in a Subarctic Estuary: a Proof of Concept from the Field

Abstract: Bacterial respiration contributes to atmospheric carbon dioxide accumulation and development of hypoxia and is a critical, often overlooked, component of ecosystem function. This study investigates the concept that maintenance respiration is a significant proportion of bacterial respiration at natural nutrient levels in the field, advancing our understanding of bacterial living conditions and energy strategies. Two river-sea transects of respiration and specific growth rates were analyzed representing low- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 47 publications
4
22
0
Order By: Relevance
“…The influence of ρ m in the control is probably underestimated. The pattern of ρ versus μ indicates a higher share of ρ m during winter conditions (Figure 3B), matching observed field value in April (1.8 fmol O 2 cell À1 d À1 , ±0.45 95% CI) (Vikström & Wikner, 2019).…”
Section: Field Patterns Between Reproduced ρ and μsupporting
confidence: 83%
See 2 more Smart Citations
“…The influence of ρ m in the control is probably underestimated. The pattern of ρ versus μ indicates a higher share of ρ m during winter conditions (Figure 3B), matching observed field value in April (1.8 fmol O 2 cell À1 d À1 , ±0.45 95% CI) (Vikström & Wikner, 2019).…”
Section: Field Patterns Between Reproduced ρ and μsupporting
confidence: 83%
“…The prokaryotic respiration rate estimates (PR) were determined by measuring oxygen in prefiltered samples (1.2 μm) with optodes during incubations as described earlier (Vikström & Wikner, 2019;Wikner et al, 2013) using an incubator box based on the Peltier element technique (±0.1 C). Four slots of the incubator box were set at 1 C, while the remaining four were set at 10 C. Briefly, 1 dm 3 sample bottles filled with <1.2 μm filtered seawater samples with a magnetic stirrer and optode stopper were inserted in the slot of the incubator box.…”
Section: Prokaryotic Respirationmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that the BGE correlates positively with the bacterial growth rates and the net primary productivity in the ecosystem ( del Giorgio and Cole, 1998 ; Alonso-Sáez et al, 2008 ). When the bacterial production decreases, a larger proportion of the consumed carbon is allocated for maintenance energy and the growth efficiency decreases ( del Giorgio and Cole, 1998 ; Eiler et al, 2003 ; Vikström and Wikner, 2019 ). Thus, a larger fraction of the consumed carbon would be respired, and a smaller fraction used for building new biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in BP or BR might cause a large variation in BGE. The maintenance respiration of bacterial cells makes up more than half of the bulk BR (Vikström & Wikner, 2019) and varies in a wide range with environmental variability (Carlson et al., 2007). Consequently, seasonal variability in BGE was more complicated than expected.…”
Section: Discussionmentioning
confidence: 99%